PEMANFAATAN ADSORBEN DARI BIJI ASAM JAWA UNTUK MENURUNKAN BILANGAN PEROKSIDA PADA CPO (CRUDE PALM OIL) - Agus Mangiring Siburian; Agnes Sartika Doharma Pardede; Setiaty Pandia (Jurnal Teknik Kimia USU, 2014)
This study was aimed to discover the effectiveness of tamarind seeds as adsorbent for the reduction of PV (Peroxide Value) in CPO (Crude Palm Oil) at the best adsorbent dose and contact time. Materials used were CPO, tamarind seeds, nitric acid, and distilled water. Variables observed were adsorbent : nitric acid ratio and oven temperature in adsorbent activation process, and contact time and adsorbent dose in adsorption process. This study was began with adsorbent modification, where the cleaced and crushed tamarind seeds to pass through 140 mesh were activated with 4 N nitric acid at 1:1, 1:2, 1:3 and 1:4 of adsorbent : nitric acid ratio while heated at 80 oC for 2 hours. Adsorbent was then dried in oven at 110 oC, 120 oC, 130 oC and 140 oC. Adsorbent with the higher iodine number was used in adsorption process that was carried out by heating 100 grams of CPO on hot plate at 90 oC with 1000 rpm of stirring speed, and followed by adsorbent addition of 0.5 %, 1,0 %, and 1,5 % (of CPO used) and 25, 35, and 45 minutes of contact time, and after that oil was filtered using vacuum pump. The study results showed that the best ratio of adsorbent : nitric acid 4 N was 1:2 at 130 oC of oven temperature with 511.773 mg/g of iodine number. The best adsorbent dose was 1.0 % at 35 minutes of contact time that gave higher reduction of PV with peroxide value of 0,00868 meq/kg with the reduction percentage was 39,72 %. This study showed that nitcic acid-activated adsorbent from tamarind seeds was effective to reduce PV in CPO.